2019
DOI: 10.3390/plants8090323
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified Heat Shock Protein90s and Polyamine Oxidases in Arabidopsis Reveal Their Interaction under Heat Stress Affecting Polyamine Acetylation, Oxidation and Homeostasis of Reactive Oxygen Species

Abstract: The chaperones, heat shock proteins (HSPs), stabilize proteins to minimize proteotoxic stress, especially during heat stress (HS) and polyamine (PA) oxidases (PAOs) participate in the modulation of the cellular homeostasis of PAs and reactive oxygen species (ROS). An interesting interaction of HSP90s and PAOs was revealed in Arabidopsis thaliana by using the pLFY:HSP90RNAi line against the four AtHSP90 genes encoding cytosolic proteins, the T-DNA Athsp90-1 and Athsp90-4 insertional mutants, the Atpao3 mutant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 93 publications
1
7
0
Order By: Relevance
“…A more detailed, molecular analysis for the interaction between PAs and Hsps has been performed in Arabidopsis thaliana [ 37 ]. Exogenous Spm increased the transcription of Hsp90 and subsequently enhanced heat tolerance.…”
Section: A Common Regulatory Mechanism Between Polyamines and Heat Sh...mentioning
confidence: 99%
See 1 more Smart Citation
“…A more detailed, molecular analysis for the interaction between PAs and Hsps has been performed in Arabidopsis thaliana [ 37 ]. Exogenous Spm increased the transcription of Hsp90 and subsequently enhanced heat tolerance.…”
Section: A Common Regulatory Mechanism Between Polyamines and Heat Sh...mentioning
confidence: 99%
“…Interestingly, silencing of the four cytosolic Hsp90 genes resulted in a significant shift of the metabolic status of polyamines. Several-fold higher levels of soluble spermidine (S-Spd), acetylated Spd (N 8 -acetyl-Spd) and acetylated spermine (N 1 -acetyl-Spm) were detected in the silenced transgenic Arabidopsis thaliana lines [ 37 ]. A loss-of-function mutant in one of the Hsps encoding genes led to an increase of polyamine oxidase activity (PAO) with a significant release of hydrogen peroxide (H 2 O 2 ).…”
Section: A Common Regulatory Mechanism Between Polyamines and Heat Sh...mentioning
confidence: 99%
“…Remarkable progress has recently been made linking PAs and other signaling molecules such as H 2 O 2 , NO, and Ca 2+ in plants ( Niu and Liao, 2016 ; Guo et al, 2018 ; Toumi et al, 2019 ; Wang et al, 2019 ; Mo et al, 2020 ). Reactive oxygen species (ROS) produced by the action of the PAO enzyme may serve as secondary messengers, whereby the upregulation of CuAO/PAO expression further raises ROS levels, resulting in the acceleration of fruit ripening ( Wang et al, 2019 ).…”
Section: Mechanisms Of Pa Action In Ripening Senescence and Qualitymentioning
confidence: 99%
“…NADPH oxidase and PAO formed a feedback loop to regulate ROS homeostasis in tobacco, which affected stress tolerance [ 17 ]. Toumi et al [ 18 ] found that under heat stress, silencing HSP90 genes resulted in an elevated level of polyamine and acetylated polyamine, leading to enhanced AtPAOs expression, and proposed that HSP90s and PAO cross-talked to influence polyamine acetylation, oxidation and ROS homeostasis. To date, there have been few reports about the interacting proteins of PAO in plants.…”
Section: Introductionmentioning
confidence: 99%